Two decades of NHRC Research. - Alejandrino, Angel A. (Philippine Engineering Journal)
The report describes how hydraulic research in the Philippines was institutionalized and made viable for the past 20 years. It considers the unique organization of the National Hydraulic Research Center, the research areas, the training aspects, the viability of NHRC, and a vision for hydraulic research. (A Professorial Chair Lecture delivered during the NHRC Colloquium held on 31 May 1993 at Room 233-A, NHRC Seminar Room, College of Engineering. U.P. Diliman, Quezon City.)